The Extent of Computational Thinking Skills Inclusion in the Content of Computer and Information Technology Course for the Third Intermediate Stage in Saudi Arabia - Barasheed, Dareen Ali; Almohammadi, Najwa Atyan (Journal of Curriculum and Teaching Methodology, 2022)
The study aimed to know the extent to which computational thinking skills are included in the content of the computer and information technology course for the third intermediate grade in Saudi Arabia. The study adopted the descriptive analytical approach (content analysis) and a content analysis card. The card consisted of four main skills of computational thinking: decomposition, algorithmic thinking, abstraction, and evaluation. The study's tool also included (30) indicators. The study used the card to analyze the content after verifying its reliability and consistency. The sample of this study involved (156) educational questions. Findings revealed that the inclusion of computational thinking skills at a high rate in the content of the computer and information technology course for the third intermediate grade in Saudi Arabia, with a frequency of (101) times and a rate of (64.7%). And the inclusion of decomposition skill is at a rate of (48.5%). And the inclusion of algorithmic thinking skill is at a rate of (23.7%). And the inclusion of evaluation skill is at a rate of (27.7%). And a lack of abstraction skill in the content. Findings also showed the existence of multiple defects. In addition, only (13) indicators were included in the content. The study recommended the adoption of computational thinking indicators within the digital technology learning document, in order to develop Saudi Arabia's computer information technology curriculums.
Keywords: Decomposition skill; Algorithmic thinking skill; Abstraction skill; Evaluation skill